Family-centered care in the perioperative area: an international perspective - Shields, Linda (Cambridge Publishing, 2007)
The terms family-centred care and perioperative care are often heard in health care, the first usually in relation to children-though it is begining to be used with other age groups and the other in relation to a particular area, the OR and perioperative environment. Family-centred care has not been formally evaluated to see if it really works, though it is commonly used by pediatric health professionals. Perioperative care is care delivered to any patient who is having surgery. This article explains how both models have come about and examines the way the two interact, with the aim of exploring the way family-centred care can be delivered in the perioperative setting.